2021
DOI: 10.1371/journal.pone.0246934
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide survey on attitudes and perceived barriers toward provision of pharmaceutical care among final year undergraduate pharmacy students in the United Arab Emirates

Abstract: Pharmaceutical care (PC) practice is still limited in the United Arab Emirates. It is crucial to understand pharmacy students’ attitudes and their perceived barriers towards PC provision, to evaluate the effectiveness of theoretical and practical curricula in creating positive attitudes toward PC. This study aims to assess attitudes of final year undergraduate pharmacy students in the United Arab Emirates (UAE), and the barriers perceived by them to practice PC. A cross-sectional survey-based study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(45 citation statements)
references
References 26 publications
2
41
0
2
Order By: Relevance
“…The majority of the studies employed a cross‐sectional survey‐based methodology ( n = 8), 28,29,31–36 while one study used a mixed‐methods study design, with a quantitative phase and a qualitative phase 30…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the studies employed a cross‐sectional survey‐based methodology ( n = 8), 28,29,31–36 while one study used a mixed‐methods study design, with a quantitative phase and a qualitative phase 30…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 provides a summary of the descriptive characteristics of the studies included in the review. The included studies were reported from Jordan ( n = 4), 29,30,34,36 Kuwait ( n = 2), 31,33 Qatar ( n = 2), 31,32 Saudi Arabia ( n = 1), 28 and United Arab Emirates ( n = 1) 35 . The target populations in all the studies were BSc pharmacy students, 28–36 and PharmD degree 34–36 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the role of the pharmacist is still poorly perceived and the lack of a consultation area or inappropriate pharmacy design were cited as the main barriers. 16 In another study, the constant occurrence of medication dispensing errors was cited as a reason for introducing safe medication dispensing training programs. 17 Another study pointed to the fundamental development of strategies to improve the quality of pharmacy services, aimed at supporting the maximum number of pharmacies, increasing the frequency of patient consultations and reducing the number of treatment errors.…”
Section: Conclusion/discussionmentioning
confidence: 99%
“…[17] Although the pharmaceutical care concept is well known to many, its systematic and comprehensive application; through the assessment and detection of medicines-related problems, constructing a pharmaceutical care plan, and follow-up evaluation are not practiced due to numerous barriers. [18,19] On the other hand, pharmacists counsel patients on the proper use of medicines, perform initial assistance to patients when needed, and discuss with patients the appropriate use of medicines considering patients' preferences and appropriately referring them to a physician when necessary.…”
Section: Discussionmentioning
confidence: 99%